Telaah Atas Ilustrasi Buku Roesdi djeung Misnem sebagai Bacaan Murid-Murid Sekolah Rakyat di Jawa Barat sebelum Perang Dunia II - H.W. Setiawan; Irma Damajanti; Prijanto Sunarto (ITB Journal Publisher, LPPM ITB, 2007)
This essay is a preliminary study on a series of book illustrations by a Dutch illustrator, the late W.K. de Bruin (1871-1945), which was printed in the book of Roesdi djeung Misnem: Boekoe Batjaan pikeun Moerid di Sakola Soenda (Roesdi and Misnem: A Reading Book for Sundanese School Pupils). As indicated by the sub-title, the so called